Programa paranaense de bioenergia: limites e possibilidades da transferência de tecnologia para a cadeia produtiva agrícola - Costa, Verlaine Lia (2015)
This dissertation aims to evaluate the process of research, innovation and technology transfer of the Bioenergy Program Paranaense for agricultural production chain. Therefore, after the construction of a theoretical contribution on the definition and historical contextualization of biodiesel, the description of the production chain and the production process, the approach of public policies for the production of biodiesel, in addition to addressing the issue of transfer of technology as well as conducting interviews with managers of the implementing bodies of the State Program institutes. Was possible to achieve the specific objectives of identifying the actions of the performers Paranaense Bioenergy Program for biodiesel production in the state; define searches in the biodiesel industry in Paraná; Technological innovations for the production of biodiesel; Technology transfer to the agricultural production chain; outline a scenario prospects and challenges for biodiesel production in the state of Paraná, and describe the process of research, innovation and technology transfer of the Bioenergy Program Paranaense for agricultural production chain. This is a qualitative research, whose research instrument was one semi-structured interviews with managers of the State Supply Office (SEAB); Paraná Institute of Technical Assistance and Rural Extension (EMATER); Parana Institute of Technology (TECPAR). The results pointed to important research in oilseed production; developing innovation, however the use of traditional technological models; and not effective technology transfer to family agricultural chain as a result of the Paranaense Program Bioenergy abandonment, although there expectations and challenges for the resumption of the program because the importance of biodiesel insertion in the energy matrix of the state.